Effects of Mo on the mechanical behavior of γ/γʹ-strengthened Co-Ti-based alloys. (15th September 2020) - Im, Hye Ji; Lee, Subin; Choi, Won Seok; Makineni, Surendra Kumar; Raabe, Dierk; Ko, Won-Seok; Choi, Pyuck-Pa
Abstract: We investigated the flow behavior of γ/γʹ-strengthened Co-12Ti and Co-12Ti-4Mo (at.%) alloys at room and elevated temperatures (up to 900°C) by electron microscopy and density functional theory. The Mo-added alloy exhibited an enhanced compressive yield strength and strain hardening behavior as compared to the reference binary alloy. This behavior could be attributed to a ~25% larger γʹ volume fraction and ~7% higher planar fault energies in Co-12Ti-4Mo. Using electron channeling contrast imaging, we observed interrupted slip bands in the Co-12Ti-4Mo alloy deformed to a strain of 6%, which led to enhanced strain hardening, in contrast to extended slip bands along {111} planes in the Co-12Ti alloy. Interrupted slip band formation in Co-12Ti-4Mo could be explained by rapid exhaustion of dislocation sources and a higher energy barrier required to cut the γʹ precipitates. These effects are due to a reduced γ channel width and substantial hardening effect of γʹ-Co3 (Ti, Mo) in the ternary alloy as well as due to the large shear modulus difference between γʹ and γ. Graphical Abstract: Image, graphical abstract